Efecto de una serie de resorcinarenos solubles en la actividad enzimática de ureasa de Jack Bean (canavalia ensiformis) - Paez Pedraza, Leidy Catherine (Universidad Antonio Nariño, 2021)
The chemical properties and molecular structure of Canavalia ensiformis urease have been extensively studied. Urease is a nickel-dependent metalloenzyme that catalyzes the hydrolysis of urea, allowing nitrogen to be available as a nutrient for plants. In agriculture, volatilization nitrogen losses and in medicine gastrointestinal diseases caused by pathogens have made the study of ureases important in several fields of application. The interaction of Jack Bean urease (JBU) with five soluble sulfonated resorcinarenes with different chemical structure was evaluated in terms of activity, interaction mechanism and simulation of molecular coupling. The results of UV-VIS spectroscopy experiments suggest conformational changes in structure that reflect the decrease in enzyme activity by more than 50%, with the strongest strong inhibitor being c-sulfonatoresorcin [4] arene (Na4ESRA), followed by c-propylsulfonaterosorcin [4] arene (Na4PrRA), c ethylsulfonatoresorcin [4] arene (Na4EtRA), c methylsulfonatoresorcin [4] arene (Na4MeRA) and the weakest inhibitor c-methylthioethylsulfonatoresorcin [4] arene (Na4SRA). Docking calculations suggest non-competitive inhibition and show that resorcinarenes bind through hydrophobic interactions to different enzyme domains and that they do not bind to the catalytic site